Effect of laser scanning speed on microstructure and corrosion resistance of TiC/AlSi10Mg composites fabricated by selective laser melting - WANG Xiaoxin; AO Min; SUN Meihui; LIU Huimin (Fenmo yejin jishu)
The TiC/AlSi10Mg composites were fabricated by selective laser melting (SLM), and the influence of laser scanning speed (600~1200 mm/s) on the microstructure, mechanical properties, and corrosion resistance was systematically investigated in this paper. The results demonstrate that the internal defects of the TiC/AlSi10Mg composites are reduced and the grain size is significantly improved with the increasing of laser scanning speed. Additionally, the dispersion characteristics of TiC particles are notably promoted. Concurrently, the hardness of the SLM-TiC/AlSi10Mg composites increases from HV(121.1±2.0) to HV(132.5±2.0). Moreover, with the progressive increase in laser scanning speed, the corrosion current density of the composites decreases from 1.57×10−6 A·cm−2 to 1.57×10−7 A·cm−2, indicating a substantial improvement in corrosion resistance.